2011
DOI: 10.1039/c1cc12239h
|View full text |Cite
|
Sign up to set email alerts
|

Efficient electrocatalytic hydrogen production from H+ ions using specially designed boron-capped cobalt clathrochelates

Abstract: Specially designed hexachlorine-containing cobalt(II) tris-dioximate clathrochelates were found to efficiently electrocatalyze the production of molecular hydrogen from H(+) ions without the overpotential of this process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 86 publications
(50 citation statements)
references
References 34 publications
(7 reference statements)
2
48
0
Order By: Relevance
“…This concept is challenging to put into practice, however, as incorporation of a redox-active ligand can have detrimental effects. For example, the delocalization of spin onto the ligand framework in Co-bisglyoxime 39,40,42 and trisglyoxime 66 catalysts have been shown to promote ligand hydrogenation 67−70 during catalysis, significantly reducing catalyst longevity.…”
Section: ■ Redox-active Ligands For Redox-leveling and Facilitating Mmentioning
confidence: 99%
“…This concept is challenging to put into practice, however, as incorporation of a redox-active ligand can have detrimental effects. For example, the delocalization of spin onto the ligand framework in Co-bisglyoxime 39,40,42 and trisglyoxime 66 catalysts have been shown to promote ligand hydrogenation 67−70 during catalysis, significantly reducing catalyst longevity.…”
Section: ■ Redox-active Ligands For Redox-leveling and Facilitating Mmentioning
confidence: 99%
“…Savéant and co-workers recently reported that in the presence 45 of strong acids, the boron-capped tris(glyoximato) cobalt clathrochelate complexes decompose to form cobalt-containing nanoparticles that are actually responsible for the observed H 2 generation activity. 50,51 In addition, considering the concerns on the homogeneous or heterogeneous nature of some water 50 oxidation cobalt catalysts published recently, 5254 we decided to investigate whether H 2 evolution detected during photolysis may come from colloidal nanoparticle or other heterogeneous cobalt species. To this end, dynamic light scattering (DLS) measurements were conducted for photolysis solutions after 0 h, 55 0.5 h, and 3 h of irradiation ( irr  455 nm) at room temperature.…”
Section: Photosensitizermentioning
confidence: 99%
“…In this regard, some cobaloxime catalysts derived from dimethylglyoxime are active electrocatalytically and operate at particularly low overpotentials (9,18,19). One of these electrocatalysts, CoðdmgHÞ 2 ðpyrÞCl (dmgH ¼ dimethylglyoximate monoanion) has also been found to be active as a hydrogen generating catalyst when combined with a suitable photosensitizer and sacrificial electron donor (6,10,20).…”
mentioning
confidence: 99%